Ex Post (In) Efficient Negotiation and Breakdown of Trade - Iyer, Rajkamal; Schoar, Antoinette (American Economic Review, 2015)
This paper examines frictions in contract renegotiation and its implications for allocative efficiency of contracts. Using a novel audit study methodology, we find that contracting parties in general are reluctant to engage in hold up. However, many efficient renegotiations of contracts also do not happen for the fear of being seen as extracting surplus. We also find that ex ante contracts are structured to mitigate losses arising from breach risk rather than hold up. The results also highlight that role of norms of fairness and reputation concerns in sustaining transactions in settings where contracts are primarily incomplete.